The Long Isoform of Intersectin-1 Has a Role in Learning and Memory - Malakooti, Nakisa (Front Behav Neurosci, 2020)
Down syndrome is caused by partial or total trisomy of chromosome 21 and is characterized by intellectual disability and other disorders. Although it is difficult to determine which of the genes over-expressed on the supernumerary chromosome contribute to a specific abnormality, one approach is to study each gene in isolation. This can be accomplished either by using an over-expression model to study increased gene dosage or a gene-deficiency model to study the biological function of the gene. Here, we extend our examination of the function of the chromosome 21 gene, ITSN1. We used mice in which the long isoform of intersectin-1 was knocked out (ITSN1-LKO) to understand how a lack of the long isoform of ITSN1 affects brain function. We examined cognitive and locomotor behavior as well as long term potentiation (LTP) and the mitogen-activated protein kinase (MAPK) and 3′-kinase-C2β-AKT (AKT) cell signaling pathways. We also examined the density of dendritic spines on hippocampal pyramidal neurons. We observed that ITSN1-LKO mice had deficits in learning and long term spatial memory. They also exhibited impaired LTP, and no changes in the levels of the phosphorylated extracellular signal-regulated kinase (ERK) 1/2. The amount of phosphorylated AKT was reduced in the ITSN1-LKO hippocampus and there was a decrease in the number of apical dendritic spines in hippocampal neurons. Our data suggest that the long isoform of ITSN1 plays a part in normal learning and memory.